1998
DOI: 10.1016/s0014-5793(98)00630-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c release and caspase activation in hydrogen peroxide‐ and tributyltin‐induced apoptosis

Abstract: The ability of H P O P and tributyltin (TBT) to trigger pro-caspase activation via export of cytochrome c from mitochondria to the cytoplasm was investigated. Treatment of Jurkat T lymphocytes with H P O P resulted in the appearance of cytochrome c in the cytosol within 2 h. This was at least 1 h before caspase activation was observed. TBT caused cytochrome c release already after 5 min, followed by caspase activation within 1 h. Measurement of mitochondrial membrane potential (v v8 8 m ) showed that both H P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
127
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(146 citation statements)
references
References 28 publications
14
127
1
4
Order By: Relevance
“…[52][53][54] These effects are due to opening of the pore complex on the mitochondrial membrane, which in normal circumstances shows a close conformation. The changes of the mitochondrial structure induce several functional alterations (collapse of the mitochondrial inner membrane potential, uncoupling of the respiratory chain, overproduction of ROS, release of ions and proteins), leading to apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] These effects are due to opening of the pore complex on the mitochondrial membrane, which in normal circumstances shows a close conformation. The changes of the mitochondrial structure induce several functional alterations (collapse of the mitochondrial inner membrane potential, uncoupling of the respiratory chain, overproduction of ROS, release of ions and proteins), leading to apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that eosinophils contain a small number of mitochondria-like structures, lacking functional respiration, but with a suggested role to participate in the apoptotic process [17]. Tributyltin (TBT) is a potent inducer of caspase activation and apoptosis in human leukaemia T cell lines and human peripheral T lymphocytes [18][19][20][21][22]. The caspase activation is preceded by early mitochondrial changes, including rapid loss of mitochondrial membrane potential (Dy m ) and release of cytochrome c. Preincubation with the adenine nucleotide translocator (ANT)-inhibitor, bongkrekic acid (BA), blocked TBT-induced mitochondrial changes and apoptosis in Jurkat cells, suggesting that TBT induces mitochondrial permeability transition (MPT) specifically in these cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…The Dy m was measured every 5 min for 20 min. TBTtreated purified lymphocytes were used as positive control cells, as it has been described previously that TBT reduces the Dy m in these cells [18]. The granulocytes were also tested for their response to the mitochondrial uncoupler carbonyl cyanide m-chlorophenyl hydrazone (CCCP) (Sigma Chemical Co, St Louis, MO, USA), a well-characterized agent known to dissipate Dy m in many cell types.…”
Section: Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…In addition, apoptosis, one of the mechanisms of cell death, is closely related to TNFα (30). TBT induces apoptosis in several kinds of cells (13)(14)(15)(16)(17)(18). We hypothesized that TBT induces apoptosis in macrophages, and that the mechanism of the apoptosis induced by TBT is related to TNFα or c-jun.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of TBT induced cell death of lymphocytes. TBT has induced apoptosis and caspase activation in human leukemia T cells (14,15), peripheral T lymphocytes (16) and rat thymocytes (17,18). However, little is known about the immunotoxicity of TBT compounds for macrophages.…”
Section: Introductionmentioning
confidence: 99%